A Review of 116 Clinical Cases Treated with External Fixators - Font, J.; Franch, J.; Cairó, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
One hundred and sixteen clinical cases (113 dogs) in which the external skeletal fixation was applied as the primary method of stabilization were reviewed. The 116 clinical cases were divided into the following groups: open fractures (41 cases); gunshot fractures (8 cases); comminuted fractures (11 cases); fractures affecting immature animals (11 cases); trans-articular application of external fixators (16 cases); corrective osteotomies (4 cases) and “simple” fractures (25 cases). History and signs of the animal (breed, age and weight), location and treatment of the fracture, healing time and functional recovery were evaluated in each case and discussed for every group. The mean healing time in the different groups ranged from 4.6 wks (immature animal’s fractures) to 13 wks (gunshot fractures). With reference to the functional recovery, in 14 cases (12.1%) the results were poor, in 57 cases (49.1%) the results were good and in 45 cases (38.3%) the results were excellent. The main complications observed were delayed union, non-union and osteomyelitis.One hundred and sixteen clinical cases of fractures (113 dogs) were treated with a »Meynard« external fixator. The cases were divided in 7 groups: open fractures, gunshot fractures, comminuted fractures, fractures affecting immature animals, trans-articular application of external fixators, corrective osteotomies and »simple« fractures. Each case is reviewed and a discussion is provided for each group.
Keywords: Dog; external skeletal fixators